2006
DOI: 10.1002/eat.20194
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of eating disorders and anxiety disorders publications (1980-2000)—part II: Statistical hypothesis testing

Abstract: Objective: The current study compared the eating disorder literature and the anxiety disorder literature in terms of statistical hypothesis testing features in 1980, 1990, and 2000. Method: Computer literature searches were conducted using PubMed and PsychInfo databases to identify relevant eating disorder and anxiety disorder articles published at each of the three time points. A total of 456 articles were randomly selected, including 228 articles each from the fields of eating disorders and anxiety disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
6
0
2
Order By: Relevance
“…Both additional CIs and p values could have been found in full texts. A study that in fact evaluated full texts, however, found similar results: Crosby et al () analyzed 152 randomly selected eating and anxiety disorder research papers from 2000 and documented CIs in 11.8% (up from 0.6% in 152 papers from 1980) and p values in 85.6% (up from 62.6% in 1980). In comparison, we found no CIs in abstracts published in 1980–1984 and, among papers with any statistical inference, in 8% in 2000–2004.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Both additional CIs and p values could have been found in full texts. A study that in fact evaluated full texts, however, found similar results: Crosby et al () analyzed 152 randomly selected eating and anxiety disorder research papers from 2000 and documented CIs in 11.8% (up from 0.6% in 152 papers from 1980) and p values in 85.6% (up from 62.6% in 1980). In comparison, we found no CIs in abstracts published in 1980–1984 and, among papers with any statistical inference, in 8% in 2000–2004.…”
Section: Discussionmentioning
confidence: 84%
“…Studies already exist on methodological problems in psychiatric articles, such as inconsistencies between test statistics and p values (Berle & Starcevic, ), deficiencies in the reporting and evaluation of blinding in psychiatric RCTs (Baethge, Assall, & Baldessarini, ), a low replication rate of psychiatric studies (Tajika, Ogawa, Takeshima, Hayasaka, & Furukawa, ), or plain statistical errors (Mcguigan, ). Although there are data on the presence of CIs in research on eating and anxiety disorders (Crosby et al, ), they are limited by the small number of articles analyzed and by the fact that the papers investigated were published between 1980 and 2000. The current and general pattern of describing statistical inference in psychiatry is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies focused on eating and psychological disorders (Crosby et al, 2006 ), psychology (Faulkner et al, 2008 ; Fidler et al, 2005 ; Fritz et al, 2012a , b ), educational psychology (Osborne, 2008 ; Sun et al, 2010 ), and learning and education (Barry et al, 2016 ) are in consonance with the results presented in this research since it was observed that the effect size analysis is not routinely used in clinical and biomedical research. However, it is important to point out that the present study was performed without applying filters related to the magazine type, impact factor, or revision criteria, such as mandatory complementary statistical test report or peer reviews.…”
Section: Discussionmentioning
confidence: 99%
“…Part II, which is reported in the accompanying article, 7 focuses on the process and procedures by which hypotheses are generated and statistically tested in scientific articles.…”
Section: Introductionmentioning
confidence: 99%